Impact of physical exercise on substance use disorders: a meta-analysis. - Dongshi Wang (Public Library of Science (PLoS), 2014)
Objective The goal of this meta-analysis was to examine whether long-term physical exercise could be a potential effective treatment for substance use disorders (SUD). Methods The PubMed, Web of Science, Elsevier, CNKI and China Info were searched for randomized controlled trials (RCT) studies in regards to the effects of physical exercise on SUD between the years 1990 and 2013. Four main outcome measures including abstinence rate, withdrawal symptoms, anxiety, and depression were evaluated. Results Twenty-two studies were integrated in the meta-analysis. The results indicated that physical exercise can effectively increase the abstinence rate (OR = 1.69 (95% CI: 1.44, 1.99), z = 6.33, p < 0.001), ease withdrawal symptoms (SMD = -1.24 (95% CI: -2.46, -0.02), z = -2, p<0.05), and reduce anxiety (SMD = -0.31 (95% CI: -0.45, -0.16), z  =  -4.12, p < 0.001) and depression (SMD  =  -0.47 (95% CI: -0.80, -0.14), z = -2.76, p<0.01). The physical exercise can more ease the depression symptoms on alcohol and illicit drug abusers than nicotine abusers, and more improve the abstinence rate on illicit drug abusers than the others. Similar treatment effects were found in three categories: exercise intensity, types of exercise, and follow-up periods. Conclusions The moderate and high-intensity aerobic exercises, designed according to the Guidelines of American College of Sports Medicine, and the mind-body exercises can be an effective and persistent treatment for those with SUD.